Association of genetic polymorphisms in the interleukin-10 promoter with risk of prostate cancer in Chinese - Liu, Jie; Song, Bao; Bai, Xueli; Liu, Wenjian; Li, Zengjun; Wang, Jialin; Zheng, Yan; Wang, Zhehai (BMC cancer, 2010)
Recent studies identified an increased risk of prostate cancer (PCa) in Caucasian men harboring polymorphisms of genes involved in innate immunity and inflammation. This study was designed to assess whether single nucleotide polymorphisms in the IL-10 promoter play a role in predisposing individuals to PCa in a Chinese population. We genotyped three SNPs of the IL-10 promoter (-1082A/G, -819T/C and -592A/C) using polymerase chain reaction-restriction fragment length polymorphism analysis in 262 subjects with PCa and 270 age-matched healthy controls. Odds ratio and 95% confidence interval were determined by logistic regression for the associations between IL-10 genotypes and haplotypes with the risk of PCa and advanced PCa grade. No significant differences in allele frequency or genotype distribution were observed for any of the IL-10 SNPs between PCa patients and control subjects. Significantly higher frequencies of -1082G, -819C and -592C allele and GCC haplotype were observed, however, in early stage patients in comparison to advanced PCa patients (for -1082 G, 13.9% vs 6.1%, OR = 2.48, P = 0.005; for -819 C 40.3% vs 30.8%, OR = 1.51, P = 0.043; for -512C, 40.3% vs 30.8%, OR = 1.51, P = 0.043; and for haplotype GCC 11.1%vs 5.1%, OR = 2.66, P = 0.008, respectively). Our results identify that IL-10 promoter polymorphisms might not be a risk factor for PCa in Chinese cohorts, but rather incidence of polymorphisms associates with PCa grade, suggesting that IL-10 expression may impact PCa progression.